THE CORRELATIONS AMONG STUDENTS’ PERCEPTIONS OF CLASSROOM ENVIRONMENT, MOTIVATION IN LEARNING ENGLISH AND THEIR ENGLISH ACHIEVEMENT OF THE ELEVENTH GRADE STUDENTS OF STATE SENIOR HIGH SCHOOLS IN INDRALAYA - ELMA FATHMAWATI; MACHDALENA VIANTY; RITA HAYATI (Sriwijaya University Learning and Education International Conference, 2016)
This study was aimed at finding out whether or not there were significantcorrelations between: (1) the students’ perceptions of classroom environment andstudents’ English achievement, (2) each scale of the students’ perceptions ofclassroom environment and students’ English achievement, (3) students’ motivationand students’ English achievement, (4) each scale of the students’ motivation andstudents’ English achievement, (5) predictor variables and criterion variable. Thisstudy also investigated whether or not there were significant contributions of thepredictor variables toward students’ English achievement. This study involved 103students selected randomly from 3 state senior high schools in 3 different subdistrictsin Indralaya. The ‘What Is Happening In this Class (WIHIC) questionnaire’,motivation questionnaire, and an English test were used to collect the data whichwere analyzed statistically by using correlation and multiple regression analyses.The findings showed that there were significant correlations between: (1) thestudents’ perceptions of classroom environment and their English achievement (r=.297), (2) five scales of the students’ perceptions of classroom environment and theirEnglish achievement, (3) the students’ motivation and their English achievement (r=.312), (4) all scales of the students’ motivation and their English achievement, (5)combination of predictor variables and criterion variable (r= .346). There were alsosignificant contributions of: (1) the students’ perceptions of classroom environmentand Teacher Support toward their English achievement, (2) the students’ motivationand Instrumental Motivation toward their English achievement, (3) predictorvariables toward criterion variable. In conclusion, the students’ perceptions ofclassroom environment and students’ motivation were significantly correlated totheir English achievement.